Da canzoni (e poesie) a canzoni : adattamenti metrici nelle traduzioni di Fabrizio de André - Valenti, Gianluca (Signa: Revista de la Asociación Española de Semiótica, 2013)
El presente trabajo reflexiona sobre las modalidades de traducción métrica de poemas a canciones, y de canciones, inglesas y francesas, asimismo a canciones en italiano. El análisis demuestra que los esquemas métricos y los patrones melódicos permanecen totalmente inalterados cuando el traductor traduce versos cantados, pero no cuando lo traducido son poemas. Además, el estudio demuestra que el idioma del texto original no afecta a las elecciones métricas del traductor. Se ha analizado el corpus lírico de Fabrizio De André. Aim of this article is to investigate the modalities of metrical translation from poems and songs to songs. To this aim I chose a subset of Fabrizio De André’s songs which are translations both from poems and from French and English songs. In particular, I show that the metrical grid and the melodic pattern are fully respected during the transposition from sung verse to sung verse; contrarily, the adaptation of poems into sung verse shows a high level of metrical freedom in the translated texts. While the language of the original text seems to barely influence the metrical grid of De André’s songs, the presence of the original melody is a major constraint in the metrical choices of the translator.